The association between meteorological parameters and the prescription patterns for asthma and allergic rhinitis, as observed in Pretoria during a one-year period - Rheeder, Paul (University of Pretoria, 2013)
Dissertation (MSc (Clinical Epidemiology))--University of Pretoria, 2006.